Cubic anatase TiO2 nanocrystals with enhanced photocatalytic CO2 reduction activity1. Issue 37 (7th May 2015) - Xu, Quanlong; Yu, Jiaguo; Zhang, Jun; Zhang, Jinfeng; Liu, Gang
<x xml:space="preserve">Abstract</x> Anatase TiO2 nanocubes with exposed 100 and 001 facets show especially high photocatalytic activity toward CO2 reduction to methane and methanol.